2007
DOI: 10.1021/jo070084v
|View full text |Cite
|
Sign up to set email alerts
|

Nitro-Substituted Stilbeneboronate Pinacol Esters and Their Fluoro-Adducts. Fluoride Ion Induced Polarity Enhancement of Arylboronate Esters

Abstract: A series of stilbeneboronate pinacol cyclic esters, containing none to three nitro groups, have been synthesized by various olefination reactions and characterized by X-ray single-crystal structure analysis. A stilbeneboronate ester bearing electron-acceptor groups experiences transition to a push-pull pi-electron system upon complexation with one fluoride ion at the boron atom. The UV-vis absorption maxima of the presented nitro-substituted stilbeneboronate esters are red-shifted upon addition of fluoride ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 62 publications
3
50
0
Order By: Relevance
“…A resonance at 173 ppm in the 13 C NMR spectra and a strong band at 1671 cm À1 in the FT-IR indicate that the carbonyl functionality is still present. A peak at 32 ppm in the 11 B NMR spectrum indicates that the boron atom exists in a three coordinate environment in solution [57]. The linear hydroboration product was confirmed by a single crystal X-ray diffraction study, Fig.…”
Section: Resultsmentioning
confidence: 80%
“…A resonance at 173 ppm in the 13 C NMR spectra and a strong band at 1671 cm À1 in the FT-IR indicate that the carbonyl functionality is still present. A peak at 32 ppm in the 11 B NMR spectrum indicates that the boron atom exists in a three coordinate environment in solution [57]. The linear hydroboration product was confirmed by a single crystal X-ray diffraction study, Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Huang et al reported that the charge on the boron atom in 2-(4-dimesitylborylphenyl)quinoline compound is significantly increased after fluoride binding and thereby the red-shifted CT transition from fluoroborate moiety to quinoline can be induced [76]. A similar red-shift in the absorption spectra after fluoride binding has also been observed in the arylboronic acid or arylboronate ester compounds [50,77]. The electronwithdrawing boronic acid or ester groups were changed into electron-donating groups upon fluoride binding, giving rise to the red-shifted ICT transition.…”
Section: Fluoride Sensing Propertiesmentioning
confidence: 78%
“…Among all the covalent functional group interactions, boronic acid stands out as the most commonly used in chemosensor construction because of its strong interactions with diols [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], aminoalcohols [20][21][22], α-amino acids [23], α-hydroxyl acids [24][25][26][27], alcohols [15,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], as well as cyanide [45,46] and fluoride [47][48][49]…”
Section: Boronic-acid-based Chemosensorsmentioning
confidence: 99%
“…Small-molecule boronolectins (SBLs) have also shown tremendous potential in carbohydrate biomarker recognition and targeting [5,58]. Several recent reviews and research papers comprehensively summarize the use of boronic acids in sensor designs for carbohydrates [9,[14][15][16]66], fluoride [47][48][49][50][51], and cyanides [45,46], and have in-depth discussions of factors [15,19,67] that should be considered in designing such sensors. In addition, there have also been quite a few reviews [8,15,66] and research papers [54,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85] on boronic acids that change their fluorescent properties upon binding to a nucleophilic analyte or pH changes.…”
Section: Boronic-acid-based Chemosensorsmentioning
confidence: 99%
See 1 more Smart Citation